Modified Strategies for Invasive Management of Acute Coronary Syndrome during the COVID-19 Pandemic - Toušek, Petr; Kocka, Viktor; Masek, Petr; Tuma, Petr; Neuberg, Marek; Novackova, Markéta; Kroupa, Josef; Bauer, David; Motovska, Zuzana; Widimsky, Petr (Journal of clinical medicine, 2020)
The COVID-19 pandemic presents several challenges for managing patients with acute coronary syndrome (ACS). Modified treatment algorithms have been proposed for the pandemic. We assessed new algorithms proposed by The European Association of Percutaneous Cardiovascular Interventions (EAPCI) and the Acute Cardiovascular Care Association (ACCA) on patients with ACS admitted to the hospital during the COVID-19 pandemic. The COVID-19 period group (CPG) consisted of patients admitted into a high-volume centre in Prague between 1 February 2020 and 30 May 2020 (n = 181). The reference group (RG) included patients who had been admitted between 1 October 2018 and 31 January 2020 (n = 834). The proportions of patients with different types of ACS admitted before and during the pandemic did not differ significantly: in all ACS patients, KILLIP III-IV class was present in 13.9% in RG and in 9.4% of patients in CPG (p = 0.082). In NSTE-ACS patients, the ejection fraction was lower in the CPG than in the RG (44.7% vs. 50.7%, respectively; p < 0.001). The time from symptom onset to first medical contact did not differ between CPG and RG patients in the respective NSTE-ACS and STEMI groups. The time to early invasive treatment in NSTE-ACS patients and the time to reperfusion in STEMI patients were not significantly different between the RG and the CPG. In-hospital mortality did not differ between the groups in NSTE-ACS patients (odds ratio in the CPG 0.853, 95% confidence interval (CI) 0.247 to 2.951; p = 0.960) nor in STEMI patients (odds ratio in CPG 1.248, 95% CI 0.566 to 2.749; p = 0.735). Modified treatment strategies for ACS during the COVID-19 pandemic did not cause treatment delays. Hospital mortality did not differ.
Keywords: acute coronary syndrome; modified treatment; outcome; COVID-19; delays